Islamic Education Model Based on Local Wisdom in Preserving Local Islamic Culture: A Comparative Study of Higher Education Institutions in Gorontalo - Naufal Ilma Wahyuddin; Hasyim Mahmud Wantu; Najamuddin Petta Solong; Mardeli Mardeli; Muhammad Rizal; Ni'ma M. Alhabsyi (FIKROTUNA: Jurnal Pendidikan dan Manajemen Islam, 2026)
The preservation of local Islamic culture requires the active involvement of higher education institutions, yet comparative studies across institutional typologies remain limited. This study compares the contributions of state-run Islamic religious universities (PTKIN) and general state universities (PTN) to the preservation of local Islamic culture in Gorontalo. It maps out the pathways of these contributions as well as the structural barriers involved. The qualitative comparative case study took place over six months (March–August 2022) at IAIN Sultan Amai Gorontalo and Gorontalo State University (UNG), covering a full academic cycle. Data were collected through in-depth interviews, field observations, and a review of institutional documents, with validity ensured through triangulation of methods, sources, and time. This study employs two analytical distinctions as analytical lenses: symbolic-normative integration (vision, philosophy, written curriculum) versus operational-transmissive integration (concrete, sustainable, and measurable mechanisms of transmission). The results show that both institutions position culture within an institutional framework, albeit with different scopes: IAIN frames it within the context of Islam and the Qur’an, while UNG encompasses Gorontalo culture more broadly. Both pursue four pathways: curricular, co-curricular, research, and community service, with varying intensities, and each excels in the pathway aligned with its orientation. The obstacles are structural in nature and were found at both institutions: limited human resources, weak coordination between units, and budgetary constraints. In the case of IAIN, the data also indicate internal ideological resistance to the relevance of cultural studies; given the limited pool of informants, this finding is presented as a proposition that still needs to be tested and is formulated as a paradox of institutional orientation. In this pair of cases, differences in mandate appear to be associated with distinct contribution profiles and with claims that are propositional in nature and require cross-site testing. These two analytical distinctions offer an initial empirical foundation for more integrated cultural preservation policies that are sensitive to the distinct characteristics of each institution